Meta‐analysis of first‐line therapies with maintenance regimens for advanced non‐small‐cell lung cancer (NSCLC) in molecularly and clinically selected populations - Tan, Pui San (Cancer Med, 2017)
Evidence has suggested survival benefits of maintenance for advanced NSCLC patients not progressing after first‐line chemotherapy. Additionally, particular first‐line targeted therapies have shown survival improvements in selected populations. Optimal first‐line and maintenance therapies remain unclear. Here, currently available evidence was synthesized to elucidate optimal first‐line and maintenance therapy within patient groups. Literature was searched for randomized trials evaluating first‐line and maintenance regimens in advanced NSCLC patients. Bayesian network meta‐analysis was performed within molecularly and clinically selected groups. The primary outcome was combined clinically meaningful OS and PFS benefits. A total of 87 records on 56 trials evaluating first‐line treatments with maintenance were included. Results showed combined clinically meaningful OS and PFS benefits with particular first‐line with maintenance treatments, (1) first‐line intercalated chemotherapy+erlotinib, maintenance erlotinib in patients with EGFR mutations, (2) first‐line afatinib, maintenance afatinib in patients with EGFR deletion 19, (3) first‐line chemotherapy + bevacizumab, maintenance bevacizumab in EGFR wild‐type patients, (4) chemotherapy+conatumumab, maintenance conatumumab in patients with squamous histology, (5) chemotherapy+cetuximab, maintenance cetuximab or chemotherapy + necitumumab, maintenance necitumumab in EGFR FISH‐positive patients with squamous histology, and (6) first‐line chemotherapy+bevacizumab, maintenance bevacizumab or first‐line sequential chemotherapy+gefitinib, maintenance gefitinib in patients clinically enriched for EGFR mutations with nonsquamous histology. No treatment showed combined clinically meaningful OS and PFS benefits in patients with EGFR L858R or nonsquamous histology. Particular first‐line with maintenance treatments show meaningful OS and PFS benefits in patients selected by EGFR mutation or histology. Further research is needed to achieve effective therapy for patients with EGFR mutation L858R or nonsquamous histology.